Composition and diversity of mucosa‐associated microbiota along the entire length of the pig gastrointestinal tract; dietary influences. (27th January 2017) - Kelly, Jennifer; Daly, Kristian; Moran, Andrew W.; Ryan, Sheila; Bravo, David; Shirazi‐Beechey, Soraya P.
Summary: Mucosa‐associated microbial populations of the gastrointestinal tract are in intimate contact with the outer mucus layer. This proximity offers these populations a higher potential, than lumenal microbiota, in exerting effects on the host. Functional characteristics of the microbiota and influences of host‐physiology shape the composition and activity of the mucosa‐associated bacterial community. We have shown previously that inclusion of an artificial sweetener, SUCRAM, included in the diet of weaning piglets modulates the composition of lumenal‐residing gut microbiota and reduces weaning‐related gastrointestinal disorders. In this study, using Illumina sequencing we characterised the mucosa‐associated microbiota along the length of the intestine of piglets, and determined the effect of SUCRAM supplementation on mucosa‐associated populations. There were clear distinctions in the composition of mucosa‐associated microbiota, between small and large intestine, concordant with differences in regional oxygen distribution and nutrient provision by the host. There were significant differences in the composition of mucosa‐associated compared with lumenal microbiota in pig caecum. Dietary supplementation with SUCRAM affected mucosa‐associated bacterial community structure along the length of the intestinal tract. Most notably, there was a substantial reduction in predominant Campylobacter populations proposing that SUCRAM supplementation of swine diet has potential for reducing meat contamination and promoting food safety.